KONSEP IJMAK MENURUT FAZLUR RAHMAN DAN PEMBAHARUAN HUKUM ISLAM - Chairul Fahmi (Universitas Islam Negeri Ar-Raniry, 2011)
The aim of this research is to find out the concept of ijmak based on Fazlur Rahman’s through. As a general rule, ijmak is understood as a source of Islamic law after al-Qur’an and hadis. Therefore, ijmak has been designed as a concret concept and its position is imposible to be wrong (infalibillitas). Moreover, it’s not available for differences of opinion among of Mujthid during the process of ijmak. Meanwhile, Fazlur Rahman believed that ijmak as a democracy process which may for every scholar (mujtahid) to make differences of opinion. This study based on library research which exploring and examining the book related to Fazlur Rahman’s thought. The result of this study stated that ijmak as a process of opinion interaction each other and will legalized through the formal institution (council/legislative).